Environmental conditions drive vocal variation in the scaled dove (Columbina squammata) - Sementili-Cardoso, Guilherme [UNESP]; Joaquim, Leonardo Marques [UNESP]; Donatelli, Reginaldo José [UNESP] (Springer Nature, 2022)
Variations in communication systems profoundly affect bird evolution. Vocalizations mediate species recognition and therefore intra-specific variation may lead to reproductive isolation, ultimately resulting in speciation. In general, vocal divergence can arise as a consequence of distinct ecological and evolutionary processes. Specifically, processes such as isolation-by-distance, allopatric isolation, and environmental variation can lead to differentiation in genes underlying song variation. We investigated vocal variation between two scaled dove subspecies, Columbina squammata squammata (Lesson, 1831) and C. s.ridgwayi (Richmond, 1896) related to environmental structure and geographic isolation. Univariate and multivariate analyses showed differences in frequency and duration of vocal features between the two subspecies. The variables peak frequency and syllable duration were distinct between subspecies. Climatic conditions and geographic isolation were associated with vocalization structure and could explain vocal divergence. The interaction between ecological factors, such as temperature and geographic distances, seems to influence vocal structure in both subspecies. Morphometric features could be confounding variables that may also explain the observed pattern of acoustic variation. These findings support the idea that spatial isolation and the environment shape vocal structure, as evidenced in these two scaled dove subspecies.
Keywords: Acoustic adaptation; Allopatric speciation; Columbidae; Environmental selection; Isolation-by-distance; Vocal structure